Fuchsine Dye Adsorption of Surface Modified Biogenic Apatite With Tryptophan and Histidine - Evren Tan; Bayram Kızılkaya (Acta Natura et Scientia)
In this study, the adsorption change of products obtained by chemical modification of waste fish bones, which are a biogenic-induced apathetic source, has been examined. Histidine (MH) and tryptophan (MT) were used for chemical surface modification, and cationic paint was used as fuchsine adsorbent. Paint adsorption was performed in water. The adsorption of MH and MT products was determined as 0.48 and 0.69 mg.g-1 in 6.76 mg.L-1 dye solution. The amount that MH and MT modified materials removed from the solution was 35.46 and 50.71%, respectively. As a result, it has been determined that the apatite-induced bones have affected the adsorption capacities of dyers as a result of different chemical molecular modifications. Additionally, it has been determined that the molecules with different qualities and properties affect the balance of adsorption. It has been observed that unprofitable products were suitable for chemical modification and adsorption procedures thanks to surface modification. With the development of studies in this field, it can be said that waste-resourced products will contribute to environmental use with effective, qualified, and useful materials.